2018
DOI: 10.1002/bit.26883
|View full text |Cite
|
Sign up to set email alerts
|

Cellular physiology controls photoautotrophic production of 1,2‐propanediol from pools of CO2 and glycogen

Abstract: Synechocystis sp. PCC 6803 PG is a cyanobacterial strain capable of synthesizing 1, 2-propanediol from carbon dioxide (CO 2 ) via a heterologous three-step pathway and a methylglyoxal synthase (MGS) originating from Escherichia coli as an initial enzyme.The production window is restricted to the late growth and stationary phase and is apparently coupled to glycogen turnover. To understand the underlying principle of the carbon partitioning between the Calvin-Benson-Bassham (CBB) cycle and glycogen in the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…But it was observed that the only 3/4 th of carbon in 1, 2-PDO was from CO2 and another 1/4 th was from glycogen, the storage energy for cyanobacteria. The homology modelling also predicted the presence of genes encoding the MG pathway in cyanobacteria (David et al, 2019).…”
Section: Genetic Manipulations For Improved 1 2-pdo Productionmentioning
confidence: 92%
“…But it was observed that the only 3/4 th of carbon in 1, 2-PDO was from CO2 and another 1/4 th was from glycogen, the storage energy for cyanobacteria. The homology modelling also predicted the presence of genes encoding the MG pathway in cyanobacteria (David et al, 2019).…”
Section: Genetic Manipulations For Improved 1 2-pdo Productionmentioning
confidence: 92%